2015
DOI: 10.1016/j.jsurg.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Resident Surgeons Underrate Their Laparoscopic Skills and Comfort Level When Compared With the Rating by Attending Surgeons

Abstract: Objective The development of operative skill during general surgery residency depends largely on the resident surgeons’ ability to accurately self-assess and identify areas for improvement. We compared evaluations of laparoscopic skill and comfort level of resident surgeons from both the resident surgeon’s and attending surgeon’s perspectives. Design We prospectively observed 111 elective cholecystectomies at the University of Michigan as part of a larger quality improvement initiative. Immediately after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 20 publications
0
9
2
1
Order By: Relevance
“…Some authors have described a tendency among surgical residents to overestimate their operative skill set, 1 whereas others have shown that residents underestimate it. [12][13][14] In specific operative skills, residents have a greater degree of confidence than suggested in earlier studies. 15 We observed that, compared with faculty ratings, residents rated their performance in most global EPAs higher than faculty ratings, but not in most operative EPAs.…”
Section: Discussionmentioning
confidence: 90%
“…Some authors have described a tendency among surgical residents to overestimate their operative skill set, 1 whereas others have shown that residents underestimate it. [12][13][14] In specific operative skills, residents have a greater degree of confidence than suggested in earlier studies. 15 We observed that, compared with faculty ratings, residents rated their performance in most global EPAs higher than faculty ratings, but not in most operative EPAs.…”
Section: Discussionmentioning
confidence: 90%
“…However, the consistent finding of residents' exaggerated perception deserves further evaluation, and the use of an assessment scale developed in our clinic could be another drawback. However, standardized criteria 4,25 were not validated for Turkish students and did not completely fulfill the items in our study.…”
Section: Discussionmentioning
confidence: 80%
“…Accuracy of self-rating was also found in other studies where residents were asked to rate their surgical performance of a laparoscopic procedure, which was then compared with the rating done by a more senior member of staff. [12][13][14] However, other studies have found that trainees tend to overestimate their own performance. 15,16 A recent review concludes that inexperienced trainees overestimate their own performance but that self-rating also depends on the type of task.…”
Section: Discussionmentioning
confidence: 98%